EXPRESSION OF THE VASCULAR ENDOTHELIAL GROWTH FACTOR AND ITS RECEPTORS (VEGFR-1 AND VEGFR-2) IN PRIMARY TUMOR CELLS IN PATIENTS WITH RENAL CANCER - D. A. Khochenkov; M. I. Volkova; I. V. Timofeev; A. S. Olshanskaya; Yu. A. Khochenkova; E. Sh. Solomko; S. A. Ashuba; V. B. Matveev (Сибирский онкологический журнал, 2021)
Purpose: to study the expression of vascular endothelial growth factor (vegf-a) and its receptors (vegfr-1 and vegfr-2) in renal cell carcinoma (rcc) cells and assess the effect of the expression levels of these markers on the tumor characteristics and prognosis of patients with rcc.Material and methods. The study included 65 patients with rcc (pt1a-t4n0/+m0/+). All patients underwent radical surgery. Histological tumor tissue samples obtained during surgery were used for the study. Expression of vegfa, vegfr-1, -2 was studied by immunohistochemical staining using appropriate antibodies to receptors and growth factors.Results. Expression of vegf and vegfr-1 and vegfr-2 receptors was ound in the cytoplasm and on the membrane of primary tumor cells of patients with rcc. There was a significant direct correlation of overexpression of the markers with g 3-4 anaplasia (vegfr-1, -2) and signs of significant tumor extension, including high pt category (vegfr-1, -2), larger size of the primary tumor (vegfr-1 , -2), tumor invasion of paranephria (vegf, vegfr-1), tumor venous thrombosis (vegfr-1, -2), multiple metastases (vegf-2), metastases in the adrenal gland (vegf, vegfr-2) and liver (vegfr-1) (p<0.05). There was a trend towards a significant effect of the level of vegf expression on the risk of progression of rcc after cytoreductive nephrectomy (p=0.0821). A tendency towards a significant effect of the level of vegfr-2 expression on the risk of death from rcc was revealed (p=0.089). No other relationships between the expression of vegf-a/vegfr-1, -2 and the prognosis of rcc were found (p>0.05).Conclusion. Expression of vegfa, as well as vegfr-1 and vegfr-2 receptors, was found on the surface and in the cytoplasm of cells of the primary tumor of patients with rcc (pt1a-t4n0/+m0/+). There was a significant correlation between vegf/vegfr overexpression with a high grade (g3-4) tumor anaplasia and significant tumor extension. In univariate analysis, a significant adverse effect on specific survival of vegfr-2 overexpression was observed. In regression analysis, vegfr-2 overexpression tended to independently affect specific survival. These results show the importance of vegf/vegfr expression as biomarkers in renal cell carcinoma.